Evaluation of cariogenic situation in children with dentoalveolar anomalies based on microbiological and biophysical indicators in oral liquid - D. A. Domenyuk; A. G. Karslieva; I. M. Bykov; A. S. Kochkonyan (Кубанский научный медицинский вестник, 2014)
Microbiological laboratory and diagnostic research methods were employed to conduct the study involving children aged 12-15 with dentoalveolar anomalies. The examination implied semi-quantitative evaluation of cariogenic bacteria Streptococcus mutans in mixed saliva and dental deposit; besides the examination covered the functional indicators in the oral liquid: salivation rate; viscosity; mineralizing potential; buffer capacity, and рН. The saliva in the patients with this dentoalveolar pathology proved to have controlled biological risk criteria for developing and intensifying caries: Strept. mutans concentration 1х106 CFU/ml; low and average buffer capacity; low and very low mineralizing potential; and pH shifted severely toward the acidic side. There has been proof offered concerning a need for comprehensive approach in evaluating the cariogenic situation, taking into account equally the clinical indicators of the oral cavity organs and tissues, physical and chemical indicators of the oral liquid, the tooth enamel, and the dental deposit.